Examining the Impact of Social Media on Youth and Its Future for History Learning (Paramita: Historical Studies Journal, 2022)
In 2022, there will be 5 billion internet users, more than 93% of whom have used social media. In the last 15 years, the existence of social media has brought changes in the way humans interact. These changes have impacted the younger generation and the world of education. Therefore, this paper aims to analyze the impact of social media on youth and its impact on education. One of the fields of education that is used for analysis is history learning. The analysis of the influence of social media in history learning is fascinating because many social media platforms currently raise issues about history. It provides an opportunity to transform historical education, which is very conventional. The existence of social media has colored the study of history, known as digital history. From a historical perspective, social media content related to history is included in the concept of digital history. In digital history, social media appears as a new variety of historiography and more relevant discussion space for students who are digital natives. Social media makes historical information sources more casual and easily accessible to students. Pada tahun 2022, tercatat 5 milyar pengguna internet dan lebih dari 93% di antaranya telah menggunakan sosial media. Dalam 15 tahun terakhir keberadaan media sosial telah membawa perubahan dalam cara manusia berinteraksi. Perubahan tersebut telah memberi dampak pada generasi muda dan dunia pendidikan. Dari pemikiran tersebut, tulisan ini bertujuan untuk menganalisis dampak media sosial terhadap kaum muda dan pengaruhnya di bidang pendidikan. Salah satu bidang pendidikan yang dijadikan analisis adalah pembelajaran sejarah. Analisis terhadap pengaruh media sosial dalam pembelajaran sejarah sangat menarik karena saat ini banyak platform media sosial yang mengangkat isu-isu tentang sejarah. Hal ini memberi peluang terhadap transformasi pendidikan sejarah yang dikenal sangat konvensional. Keberadaan media sosial telah memberi warna baru dalam studi sejarah yang disebut sebagai sejarah digital. Dalam perspektif sejarah, konten sosial media yang berhubungan dengan sejarah termasuk dalam konsep sejarah digital. Sebagai sejarah digital, media sosial tampil sebagai ragam baru historiografi dan ruang diskusi yang lebih relevan bagi siswa yang termasuk dalam digital native. Dengan media sosial, sumber informasi kesejarahan tampil lebih casual dan mudah dijangkau oleh siswa. Cite this article: Singh, L., Ahmad, T.A. (2022). Examining the Impact of Social Media on Youth and Its Future for History Learning. Paramita: Historical Studies Journal, 32(2), 253-262. http://dx.doi.org/10.15294/paramita.v32i2.35055